Analisis Strategi Pemasaran Handmade Tas UMKM AKA di Kelurahan Bubulak Kabupaten Bogor - Lalu Hendri Setiawan; I Wayan Budiastra (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The purpose of this research is to find out the factors that are the strengths, weaknesses, opportunities, and threats of AKA UMKM bag handicraft as well as knowing what strategies should be carried out for marketing based on these factors. The data analysis technique used is the SWOT analysis. SWOT analysis is done by identifying and analyzing internal and external factors that influence the basic components of the SWOT analysis. Strategies that can be applied in marketing AKA UMKM bag crafts are SO (Strength-Opportunity) Strategyby increasing the craftsmen's human resources in order to improve product competitiveness and strengthen capital, promote and maintain good relations with suppliers to ensure the continuity of raw materials. WO (Weakness-Opportunity) strategy by optimizing the use of various media in increasing the promotion and utilization of government facilities to increase innovation, capital, production management, and marketing. ST (Strength-Treath) strategy through increasing product efficiency and maintaining consumer confidence with guaranteed quality through good production management. WT (Weakness-Treath) strategy by increasing product innovation and promotion by observing market developments and improving production data records. AKA UMKM have not been maximized in implementing SWOT combination strategies so that their application needs to be improved in the future so that AKA UMKM will be more developed. Kata Kunci: AKA UMKM, bag craft, SWOT analysis